2009
DOI: 10.2331/suisan.75.365
|View full text |Cite
|
Sign up to set email alerts
|

Food habits of fish communities in a Sargassum confusum bed off the coast of Ishikari, Hokkaido, Japan

Abstract: Seasonal changes in the composition and food habits ofˆsh communities in a Sargassum confusum-dominated bed oŠ the coast of Ishikari, Hokkaido, Japan were examined. Twenty-seven species, a total of 997 individuals, were collected by beach seine surveys from June 2002 to August 2003. Numbers of individuals and species increased in spring to fall compared to winter. A cluster analysis based on stomach contents composition showed that theˆsh communities comprised eight feeding groups: A) phytal amphipods, B) phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Their meadow plays important roles in coastal ecosystems. For example, experiments by Levin and Hay (1996) suggested that the Sargassum meadow has a sh aggregation effect, and it was reported that the number of migrating sh decreased with a decrease the Sargassum meadow in Hokkaido (Sakurai et al 2009). Sargassum meadow also serves as food for abalone and other useful shery species (Uki et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Their meadow plays important roles in coastal ecosystems. For example, experiments by Levin and Hay (1996) suggested that the Sargassum meadow has a sh aggregation effect, and it was reported that the number of migrating sh decreased with a decrease the Sargassum meadow in Hokkaido (Sakurai et al 2009). Sargassum meadow also serves as food for abalone and other useful shery species (Uki et al 1986).…”
Section: Introductionmentioning
confidence: 99%